Properties impact from wastewater treatment sludge utilized into fired clay bricks - Abdul Kadir, Aeslina; Abdul Salim, Nurul Salhana; Al Bakri Abdullah, Mohd Mustafa; Mohd Nawi, Mohd Nasrun; Sandu, Andrei Victor (Construction Research Institute of Malaysia (CREAM), 2017)
Disposal of wastewater treatment plant sludge waste into landfills has become a serious threat to the global environment due to the massive generated every year.Nevertheless, a relevant alternative solution could be developed as recently rapid growing interest in the usage of sludge material to the manufacturing of fired clay brick has been observed.The utilization of these waste materials in fired clay bricks usually has positive effects on the properties such as lightweight bricks with improved shrinkage, porosity, and strength. The primary objective of this study is to focus on the properties impact of the wastewater treatment sludge incorporated into fired clay bricks.The characteristics of raw materials obtained by using the X-ray Fluorescence Spectrometer showed that the chemical composition of the raw materials of clay soil and wastewater treatment sludge was high with silicon dioxide and with the same chemical composition Type A and Type B of wastewater treatment sludge are suitable to replace clay soil as raw materials.The recommended percentage of wastewater treatment sludge incorporation was up to 20% with better physical and mechanical properties.The physical and mechanical properties were tested according to BS 3921:1985.The results showed that the utilization of Type A and Type B into brick manufacturing complied with BS 3921:1985 standard requirements.Therefore, wastewater treatment sludge can be material for brick production with appropriate mix and design and as an alternative environmentally friendly disposal method.